Análisis Citoquímico-Microbiológico de Líquido Peritoneal en el Estudio de Exudados y Trasudados - Figueroa Yépez, Bryan Wladimir (2021)
ABSTRACT Ascites is a pathological collection of peritoneal fluid that can be seen very frequently. Its causes are due to many factors, but they mainly interfere with significant hormonal and volumetric dysregulation in the context of portal hypertension. Ascites is associated with numerous complications, including spontaneous bacterial peritonitis, hepatohydrothorax, and hepatorenal syndrome. The research objective was to study the importance of the cytochemical-microbiological analysis of the peritoneal fluid in exudates and transudates. The methodology was based on a bibliographic study using descriptive and documentary analysis of the last five years that is focused on the importance of knowing how to differentiate peritoneal effusions because of exudate or a transudate to diagnose the different causes of this disease, by cytochemical analysis of the fluid found in the peritoneal cavity. In addition, an updated study was carried out to differentiate transudate and exudate liquids with the help of biochemical methods, in which the great benefit of the cell count is raised, for the research several problems that exist are analyzed, especially to differentiate the types of effusions and that of some biochemical markers that help to understand the parameters of exudate as well as a transudate; Therefore, the corresponding procedures for this type of event are identified so that they can be applied in a clinical laboratory in order to obtain concrete and reliable results, always maintaining the well-being of the patient. Keywords: peritoneal effusion, exudate, transudate. Reviewed by: Mgs. Sonia Granizo Lara. English professor. c.c. 0602088890